INDIKASI PERSENGKOKOLAN DALAM TENDER - Edi Krisharyanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Before doing big and highly amount projects invested by APBN or APBD, bids are often previously executed. However, along with the increase of participant and the business it self, any kinds and signs of collution is some possible things to find.